2014
DOI: 10.6001/actamedica.v20i4.2815
|View full text |Cite
|
Sign up to set email alerts
|

Methods of main bronchus stump closure and incidence of bronchopleural fistula after pneumonectomies for lung cancer (a retrospective single center review)

Abstract: Background. Bronchopleural fistulas (BPFs) development after pneumo nectomy remains a serious complication and is associated with high mortality rate. We evaluated incidence and risk factors, that influenced BPF rate after pneumonectomies for lung cancer patients treated at the Department of Thoracic Surgery and Oncology of the Institute of Oncology, Vilnius University, and compared different bronchial stump suturing techniques. Methods. It is a retrospective study. We reviewed 580 lung cancer patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nevertheless, the superiority of stapler over manual sutures in preventing BPF remains controversial (12). Several studies have reported a lower incidence of BPF after stapler closure compared to manual suturing (11,22,23), while others report a similar incidence between both techniques (24). Beyond the scope of this paper, in recent years, videoassisted thoracic surgery (VATS) pneumonectomy has been performed in selected cases (25), which requires the use of staplers in most situations (26).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the superiority of stapler over manual sutures in preventing BPF remains controversial (12). Several studies have reported a lower incidence of BPF after stapler closure compared to manual suturing (11,22,23), while others report a similar incidence between both techniques (24). Beyond the scope of this paper, in recent years, videoassisted thoracic surgery (VATS) pneumonectomy has been performed in selected cases (25), which requires the use of staplers in most situations (26).…”
Section: Discussionmentioning
confidence: 92%
“…It affects 1.5-12.5% of NSCLC patients undergoing pneumonectomy (5,8,9), leading to lifethreatening complications, such as respiratory insufficiency, pneumonia, empyema, and sepsis in the remaining lung. Furthermore, 13-67% of individuals who develop BPF after pneumonectomy dies within 30 days after the operation (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation